Selective intraarterial radionuclide therapy with yttrium-90 (Y-90) microspheres for hepatic neuroendocrine metastases: Initial experience at a single center - Arslan Nuri; Emi Mustafa; Alagöz Engin; Üstünsöz Bahri; Oysul Kaan; Arpacı Fikret; Uğurel Şahin; Beyzadeoğlu Murat; Özgüven Ali Mehmet (Vojnosanitetski Pregled)
Background/Aim. Selective intraarterial radionuclide therapy (SIRT) with Yttrium-90 (Y-90) microspheres is also known as radioembolization and delivers high doses of radiation to hepatic tumors with minimum healthy liver exposure. The aim of this study was to present our preliminary experience in the role of liver directed radiotherapy with Y-90 microspheres for the treatment of unresectable hepatic metastases from neuroendocrine tumors (NET). Methods. The results of SIRT in 10 patients (5 males, 5 females; mean age 48.7 years; age range 24-73 years) with metastatic liver disease from NETs during the period from April 2008 through August 2010 were reviewed. All patients had meticulous pre- and post-imaging studies as a part of their work-up procedure, as well as serologic tests of liver function to determine the extent of liver function damage. The patients who were eligible for SIRT had pretreatment visceral angiography to define and occlude non-target arteries. Results. The mean ± SD administered SIR-Spheres® activity was 1.49 ± 0.42 GBq (range 0.72-2.21 GBq) in all the patients. These treatments delivered a dose of 99.73 ± 66.36 Gy (range 49- 420.8 Gy) to the target tumors. The estimated dose to the lungs and normal liver was 4.45 ± 1.95 Gy (range 2.4-8.5 Gy) and 26.73 ± 14.19 Gy (range 5-58.9 Gy), respectively. Overall response rate of 90% and patient tolerance was satisfactory for most patients. Conclusion. From our limited experience, we can conclude that SIRT with Y-90 microspheres is a safe and efficacious treatment option for patients with liver metastasis of NET without any serious side effects.